Diskresi Hukum dalam Pemberian Dispensasi Perkawinan - Emanuel Boputra (JURNAL HUKUM, POLITIK DAN KEKUASAAN, 2020)
Marriage is one important part in the journey of human’s life. According to the Law No. 1 of 1974 concerning Marriage, Article 1: Marriage is a physical-mental bond between a man and a woman, as a husband and a wife, aiming to create an eternal and happy family/household based on God Almighty. Marriage aims to create a happy and eternal family/household.Article 7 (1) of the Marriage Law stipulates and regulates the age limit for a marriage. A marriage is allowed when the man is at least 19 (nineteen) years old, and the woman is at least 16 (sixteen) years old. Next in the verse 2 is stated that in the event of deviating the verse 1, this article is able to request a dispensation from the Court or other Officials which is appointed by both the parents of the man and the woman. Therefore, a dispensation from the Court or other Officials, which is appointed by both the parents of the man and the woman, is required in order to hold a marriage if those minimum ages are not attained yet.Indeed, a dispensation is able to be justified based on the law aspect (a dispensation is required from the Court or other Officials, appointed by both the parents of the man and the woman, if those minimum ages are not attained yet). The submission of an application for the marriage dispensation to the Court is a legal step, chosen by the applicant in order to legalize their marriage. However, the space for dispensing various forms of child marriage is in fact a form of violation towards the children’s rights, as stated in the legal consideration of the Decree of the Constitutional Court of the Republic of Indonesia No. 22/PUU-XV/2017.